Design of Rectangular Compensation Mechanism based on the Cross Double-slider Model - Shu Zhiwei; Chen Xinyuan; Zhan Xiaohui; Deng Jianghong (Jixie chuandong)
The cross double-slider model is put forward to solve the defect of that continuous casting mold material area is rectangular,while the ordinary double pendulum rod type automatic mold flux feeder machine material area is sector,there is a blind zone of feeding. And the mathematical model of the cross double-slider model is established,the equation of cam contour curve is calculated,the reason of the dead center that the design based on the cross double-slider model is analyzed. On the basis of the above,the rectangular compensation technology of cam linkage combined mechanism is put forward,the virtual prototype of cam linkage combined mechanism is established,and the kinematics analysis of the virtual prototype is carried out. The speed curve of the center of outlet port of the feed tube is obtained,which provides the basis for improving the uniformity of the protection slag in the crystal. And the virtual prototype is analyzed,and the minimum transmission angle of mechanism is obtained,the feasibility of the design parameters of the virtual prototype is verified.